Pharmacological Inhibition of MALT1 Ameliorates Autoimmune Pathogenesis and Can Be Uncoupled From Effects on Regulatory T-Cells - Biswas, Subhabrata; Chalishazar, Aditi; Helou, Ynes; DiSpirito, Joanna; DeChristopher, Brian; Chatterjee, Devin; Merselis, Leidy; Vincent, Benjamin; Monroe, John G.; Rabah, Dania; Long, Andrew J. (Frontiers in Immunology, 2022)
MALT1 forms part of a central signaling node downstream of immunoreceptor tyrosine-based activation motif (ITAM)-containing receptors, across a broad range of immune cell subsets, and regulates NF-kB driven transcriptional responses via dual scaffolding-protease activity. Allosteric inhibition of MALT1 activity has demonstrated benefit in animal models of inflammation. However, development of MALT1 inhibitors to treat autoimmune and inflammatory diseases (A&ID) has been hindered by reports linking MALT1 inhibition and genetic loss-of-function to reductions in regulatory T-cell (Treg) numbers and development of auto-inflammatory syndromes. Using an allosteric MALT1 inhibitor, we investigated the consequence of pharmacological inhibition of MALT1 on proinflammatory cells compared to regulatory T cells. Consistent with its known role in ITAM-driven responses, MALT1 inhibition suppressed proinflammatory cytokine production from activated human T-cells and monocyte-derived macrophages, and attenuated B-cell proliferation. Oral administration of a MALT1 inhibitor reduced disease severity and synovial cytokine production in a rat collagen-induced arthritis model. Interestingly, reduction in splenic Treg numbers was less pronounced in the context of inflammation compared with naïve animals. Additionally in the context of the disease model, we observed an uncoupling of anti-inflammatory effects of MALT1 inhibition from Treg reduction, with lower systemic concentrations of inhibitor needed to reduce disease severity compared to that required to reduce Treg numbers. MALT1 inhibition did not affect suppressive function of human Tregs in vitro. These data indicate that anti-inflammatory efficacy can be achieved with MALT1 inhibition without impacting the number or function of Tregs, further supporting the potential of MALT1 inhibition in the treatment of autoimmune disease.